Penerapan media hedbanz dengan tema essen und trinken untuk keterampilan berbicara bahasa jerman bagi siswa SMA - Nugrahantie, Putri; Indriwardhani, Sri Prameswari (Fakultas Sastra, 2023)
Abstrak: : This study intends to describe the implementation of Hedbanz for German speaking skill with 'Essen und Trinken' theme for XI IPS 4 Students of SMAN 9 Malang and to describe the students' responses. The method used is descriptive-qualitative. The data are collected through observation sheets and questionnaires. Based on the results of the observation sheet, the implementation of Hedbanz media went according to plan. Observers stated that most students can ask each other to use Ja/Nein Fragen. The students stated that Hedbanz can be used independently. Overall, they responded positively to the implication of Hedbanz. In conclusion, Hedbanz can be utilized as an alternative German learning media, especially for speaking. Kata Kunci: Hedbanz, Speaking, German